2011
DOI: 10.1007/s10228-011-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Scorpaena jacksoniensis and a redescription of S. cardinalis, a senior synonym of S. cookii (Scorpaeniformes: Scorpaenidae)

Abstract: The Scorpaena cardinalis complex, including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Growth-related changes in the relative lengths of some body parts are well documented for several members of the Scorpaenidae (e.g., Motomura et al 2005bMotomura et al , c, 2006bMotomura et al , 2011. Analyses of 51 measurements in P. brevipectoralis indicates that body depth at the anal-fin origin, caudal-peduncle length and depth, and the lengths of almost all fin rays tend to decrease as a percentage of SL with growth ( Fig.…”
Section: Pterois Brevipectoralismentioning
confidence: 68%
“…Growth-related changes in the relative lengths of some body parts are well documented for several members of the Scorpaenidae (e.g., Motomura et al 2005bMotomura et al , c, 2006bMotomura et al , 2011. Analyses of 51 measurements in P. brevipectoralis indicates that body depth at the anal-fin origin, caudal-peduncle length and depth, and the lengths of almost all fin rays tend to decrease as a percentage of SL with growth ( Fig.…”
Section: Pterois Brevipectoralismentioning
confidence: 68%
“…Decreasing length of fin rays with growth has already been reported for several members of Scorpaenidae, e.g., Scorpaena spp. (Motomura et al 2005c(Motomura et al , 2011b and Pterois brevipectoralis (Mandrytsa 2002) .…”
Section: Discussionmentioning
confidence: 99%
“…pele Eschmeyer and Randall, 1975;S. scrofa Linnaeus, 1758;and S. sumptuosa Castelnau, 1875, examined in this study are listed in Motomura et al (2005aMotomura et al ( , b, 2006Motomura et al ( , 2007Motomura et al ( , 2009Motomura et al ( , 2011, Motomura and Senou (2008), and Wibowo and Motomura (2019).…”
Section: Introductionmentioning
confidence: 87%
“…Examination of all available type and non-type specimens regarded as valid Indo Pacific species of Scorpaena, in addition to the original descriptions, revealed that they could be separated into three groups, based on the condition of the lateral lacrimal spine. Those lacking the spine included eight species [S. bulacephala Yearsley, 2005, S. colorata (Gilbert, 1905), S. decemradiata Fricke, Golani, Appelbaum-Golani and Zajonz, 2018, S. gasta Motomura, Last and Yearsley, 2006, S. neglecta Temminck and Schlegel, 1843, S. papillosa (Schneider and Forster, 1801), S. scrofa Linnaeus, 1758and S. sumptuosa Castelnau, 1875; those with two points on the spine, three species (S. cardinalis Solander and Richardson, 1842, S. jacksoniensis Steindachner, 1866and S. orgila Eschmeyer and Allen, 1971; and those with a single point, the six remaining species (S. miostoma, S. brevispina Motomura and Senou, 2008, S. lacrimata Randall and Greenfield, 2004, S. onaria Jordan and Snyder, 1900, S. pepo Motomura, Poss and Shao, 2007and S. pele Eschmeyer and Randall, 1975) (Eschmeyer and Randall 1975;Randall and Greenfield 2004;Motomura et al 2005aMotomura et al , b, 2006Motomura et al , 2007Motomura et al , 2009Motomura et al , 2011Motomura and Senou 2008;Fricke et al 2018;Wibowo and Motomura 2019; this study). However, S. miostoma can be distinguished from other species in the third group by having relatively lower numbers of pectoral-fin rays (15-17, usually 16; rarely 15 or 17, 3 and 8 specimens of all examined specimens, respectively) (vs. 16-17; usually 17 in the other species, except for S. pepo) (Eschmeyer and Randall 1975;Randall and Greenfield 2004;Motomura et al 2006;Motomura and Senou 2008), scale rows in the longitudinal series (43-47, usually 45) (vs. 61 in S. lacrimata;…”
Section: Introductionmentioning
confidence: 99%